Republic of Poland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2008)
This paper provides three policy lessons to take full advantage of the opportunity afforded by EU funds. The main features of the global integrated monetary and fiscal (GIMF) model and how it was modified to account for income convergence are discussed. The impact of EU funds as exhibited in the model and highlights potential risks related to the authorities' policy choices, in particular in the fiscal area, are also discussed. The macroeconomic literature on the impact of EU funds can be divided into broad groups: model simulations and econometric studies.